Pengembangan Lembar Kerja Siswa (LKS) Pengetahuan Deklaratif Pada Materi Hidrokarbon - Dian Novita, (Pendidikan Sekolah Dasar, 2009)
Research has been conducted to determine the feasibility LKS declarative knowledge on subject matter of the suitability of hydrocarbons are reviewed with a criteria component LKS and LKS content criteria through the desk evaluation.Type of research is the development of research 4D model learning device are defining, design, develop, and disseminate according to Thiagarajan (in Ibrahim, 2001). In this research, only three stages that is; define, design, and develop. Conditions of eligibility according Riduwan (2007), if the score reaches =, 61% and the results showed that LKS-oriented model of declarative knowledge has been feasible to use direct teaching learning process. This is evidenced by the results of the assessment criteria sheet component of 78.82% for the LKS one with a strong category; 78.35% for the second worksheet with the strong category, and 78.82% for category sheet with a strong third. LKS contents of 79 criteria, 47% for the LKS one with a strong category; 79.73% for the second worksheet with the strong category, and 78.13% for category sheet with a strong third.